Biópsia transbrônquica em pneumonite de hipersensibilidade crônica - Botelho, Andre Bezerra [UNIFESP] (2019)
Introduction: The diagnosis of chronic hypersensitivity pneumonitis (cHP) is based on clinical data, tomographic patterns and, in several cases, on pathologic findings. There are some proposed diagnostic criteria, but none is widely accepted. The role of transbronchial biopsy (TBB) in HP is still uncertain. Aim: To analyze the yield of the TBB in patients with cHP according tomographic findings and to evaluate the importance of the bronchoalveolar lavage (BAL) in the diagnosis approach. Methods: Retrospective study of patients with cHP submitted to TBB in two specialized centers in interstitial lung diseases in São Paulo - Brazil, between 1999 and 2017. Diagnostic criteria according Salisbury et al were applied to diagnosis. The disease was classified as non-fibrotic or fibrotic according findings of fibrosis on HRCT. Findings in TBB were classified as definitive (granulomas and/or multinucleated giant’s cells, associated or not with peribronchiolar infiltration of lymphocytes and plasma cells and bronchiolocentric distribution) and compatible (indicative of small airway injury, such as peribronchiolar metaplasia, organizing pneumonia and intra-alveolar xanthomatous macrophages). Results: One hundred and nine patients were included, with female predominance (70.6%), mean age 61.4 years and mean FVC 72.1%. The main symptom was dyspnea, in 95 cases (87.1%). The tomographic finding more common was ground-glass, in 90 cases (82.6%), followed by any indicative findings of fibrosis, in 76 (69.7%) and mosaic attenuation/air trapping, in 67 (61.5%). The main identified exposures were to molds (60.6%) and birds (48.6%). The presence of definitive findings of HP were seen in 15 cases (13.8%) and compatible findings in 33 (30.2%), with total yield of 44%. Pathologic definite findings were more common in cases without fibrosis on HRCT (24,2% vs. 9,2%, p= 0.036), whereas the presence compatible findings were more common in fibrotic HP (38.1% vs. 12.1%, p= 0.007). The number of samples obtained in the TBB did not influences the results. 52 patients had differential cytology of the BAL. Lymphocytosis (> 20%) was present in 51.9% of the patients. The median of the percentage of lymphocytes in the BAL was 20,0% (interquartile interval: 11,5% to 29,5%). There wasn’t difference in the median of the lymphocytes according tomographic patterns. Conclusion: The TBB has a considerable yield to the diagnosis of HP and in association with BAL should be used as the initial option in the investigation of the disease.